Indexing and storage techniques for satellite images in a parallel architecture - Wu, Li (2008)
This thesis investigates multi-dimensional indexing techniques for content-based image retrieval, proposes a new indexing structure for an extended framework of features with varying dimensions/lengths, develops an effective approximative indexing strategy, and brings forward an effective de-clustering approach for a cluster architecture.